Trend of homicide mortality in a municipality of São Paulo, during the period from 2000 to 2020 (Research, Society and Development, 2022)
The aim of this study was to analyze the trend of the homicides rate in a region of São Paulo (2000-2020). Ecological study of temporal trend. Data about age, sex, race/color and region of residence were extracted from the Mortality Information System (SIM) and were analyzed by descriptive statistics and control graphics. The control graphics defined zones A (control - inclusion of 99,7% of the data), B (vigilant - 95,4%) and C (central - 68,3%). The limits of each one of these zones were calculated considering the negative binominal distribution. The number of homicides deaths were evaluated by: one of the rates above the superior/inferior control line, at least six consecutive increasing/decreasing points, at least nine consecutive points at the same side (above/below) of the average, two of three consecutive points at some of the A Zones and four of five consecutive points at any of the B Zones or beyond. From 2000-2020 there were 5.185 homicides with a rate (100.000 inhabitants) of 55,78 in 2000, 59,42 in 2001 and decreasing until 2009 (13,80). The age range with the greatest rate was of 20 to 40 uncompleted years old, being below the period average since 2006. The gender with greatest risk was male, showing rates below the period average since 2006 as well. White people were the ones who predominantly suffered homicides. East, Southwest and South regions showed occurrences below average since 2007. It is mandatory to know the trend and distribution of homicide mortality to better lead Public Policies.